Ursodeoxycholic acid can be used as a steroid-tapering drug in the treatment of autoimmune hepatitis - Rukiye VARDAR; Galip ERSÖZ; Zeki KARASU; Ulus S. AKARCA; Yücel BATUR (Turkish Journal of Gastroenterology, 2019)
-